Yield and quality of screenhouse-grown radish (Raphanus sativus cv. Everest F1) under various compost amendments - Millado, Cyrose Suzie Silvosa; Macapeges, Amina Risha A.; Abad, Reynaldo G.; Bayogan, Emma Ruth V. (2019)
Organic farming aims to restore biodiversity by prevention of synthetic chemical toxicity using natural nutrient amendments such as composts and use of companion plants for pest control instead of synthetic pesticides. In Mindanao, radish is cultivated mostly as a vegetable root crop, but when needed, it can also serve as a companion plant for pest control on other crops. In this study, growth and development of potted radish (Raphanus sativus cv. Everest F1) in a screenhouse were evaluated under a two-factor completely randomized design with light intensity and compost amendments as factors. At seedling stage, 10% Tacunan and 20% DA Vermicompost in the potting mix resulted to high germination while Dr. Bo's Biofertilizer in the mix decreased germination rate. At seedling stage, amendment of 20% Dr. Bo’s Biofertilizer resulted to longest shoots. At harvest stage, amendment of Dr. Bo’s Biofertilizer increased shoot length and shoot fresh weight. Harvested taproots, however, were longest and heaviest from potting mix amended with 20% DA or 20% Tacunan Vermicompost. Furthermore, the negative control consistently gave poorest shoot and root growth and was seen to be the most pest-infected plants.
Keywords: Mindanao studies